Amelioration of experimentally induced inflammatory arthritis by intra-articular injection of visnagin - Sowmyasree Gurram; Pratibha Anchi; Biswajit Panda; Sayali Santosh Tekalkar; Ravindra Bapu Mahajan; Chandraiah Godugu (Elsevier, 2022)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease characterized by synovial hyperplasia, cartilage destruction and bone erosion. Visnagin (VIS) is a proven anti-inflammatory agent and in this study, we aimed to evaluate the anti-arthritic activity of VIS when administered via intra-articular (I.A.) route of administration. Materials and methods: RAW 264.7 ​cells were stimulated with lipopolysaccharide (LPS) (1 ​μg/mL) and treated with VIS at concentrations of 12.5 and 25 ​μM. Arthritis was induced in Sprague Dawley rats by administering Complete Freund's Adjuvant (CFA) (1 ​mg/mL) through (I.A.) route and treated with VIS via (I.A.) route at doses of 3 and 10 ​mg/kg twice a week for 3 weeks. Protective effects were assessed by arthritic score, behavioral studies for pain evaluation, radiological assessment, histopathological examination and molecular studies. Results: Our results indicated that VIS significantly reduced LPS induced inflammation in RAW 264.7 ​cells. While in arthritic rats, VIS reduced the disease scorings with improvement towards pain. Pathological examination demonstrated that VIS reduced knee joint inflammation and cartilage destruction. Radiographic analysis and molecular studies also supported the protective effects of VIS. Conclusion: The results of the study imply that VIS exerted potential anti-inflammatory and anti-arthritic activity in in vitro and in vivo models of RA.